An Investigation into the Impact of Visual Teaching and Learning Strategies on Undergraduate Students’ Self-reported Experience of Quantitative Research Methods Teaching - Marty Chamberlain (European Sociological Association 11th Annual Conference, 2013)
This paper details the findings of research conducted to identify the impact if the use of visual learning and teaching resources on undergraduate students statistical anxiety, It highlights that although a useful learning tool, they are a number of broader factors which dominate the teaching and learning process.